Factors inhibiting effective delegation in public organization: A case study of Kibaha Education Centre - Swai, Lucy (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management (SOPAM) in partial fulfilment of the requirements for the award of the degree of Master of Science in Human Resource Management (Msc.HRM) of Mzumbe University, Tanzania